Asset protection and security management handbook (Auerbach Publications, 2003)
The Asset Protection and Security Management Handbook is a must for all professionals involved in the protection of assets. For those new to the security profession, the text covers the fundamental aspects of security and security management providing a firm foundation for advanced development. For the experienced security practitioner, it provides the tools necessary for developing effective solutions and responses to the growing number of challenges encountered by today's security professionals. Based on the ASIS asset protection course, the text provides information vital to securit.